Ecological overview of hard ticks (Ixodida: Ixodidae) in Nagasaki prefecture of western Japan during winter 2021–2022 - Tomonori Hoshi; Erina Ishigaki; Thanawat Khongyot; Satoshi Kaneko (Scientific Reports)
Abstract In Japan, Japanese spotted fever, Lyme disease and severe fever with thrombocytopenia syndrome caused by Ixodidae species are endemic. To prevent and control the diseases, fundamental understandings in tick ecology are crucial. Hence, this study aimed to analyse tick species richness and abundance across Nagasaki prefecture including its remote islands from a wide range of environments. A total of 74 sampling points screening during winter 2021–2022, using dragging method resulted in 14,883 tick samples (279 adults, 7148 nymphs and 7456 larvae) in 11 species belonging to four genera. Haemaphysalis flava dominated adult populations, while H. formosensis was predominant among nymphs. Both species are possible vectors of Japanese spotted fever and severe fever with thrombocytopenia syndrome. The ecological analysis revealed more complex species distribution in the remote islands compering to the main island in both adults and nymphs. In addition, the ground temperature was a significant regulatory factor for both adults and nymphs. The research provides valuable insights on tick distributions, ecological groupings and environmental preferences in Nagasaki. These findings contribute to the fundamental understanding of tick ecology and could contribute to design strategies for tick population control and tick-borne disease prevention in Nagasaki or possibility to nearby areas.